2011
DOI: 10.1016/s1470-2045(11)70232-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crizotinib on overall survival in patients with advanced non-small-cell lung cancer harbouring ALK gene rearrangement: a retrospective analysis

Abstract: Summary Background ALK gene rearrangement defines a new molecular subtype of non-small-cell lung cancer (NSCLC). In a recent phase 1 clinical trial, the ALK tyrosine-kinase inhibitor (TKI) crizotinib showed marked antitumour activity in patients with advanced, ALK-positive NSCLC. To assess whether crizotinib affects overall survival in these patients, we did a retrospective study comparing survival outcomes in crizotinib-treated patients in the trial and crizotinib-naive controls screened during the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
540
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 813 publications
(559 citation statements)
references
References 31 publications
13
540
2
4
Order By: Relevance
“…164 In a recent analysis of 82 ALK-positive lung cancer patients, ALK tyrosine kinase inhibitor (crizotinib) therapy was associated with improved survival compared with that of crizotinib-naive controls. 166 Survival among ALK-positive patients who were given crizotinib in the second-line or third-line setting was significantly better than those patients given any second-line therapy (2-year survival, 55 vs 12%). However, unlike EGFR mutation, ALK rearrangement was not a favorable prognostic factor.…”
Section: Eml4-alk Rearrangement: Driver Mutation Of Lung Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…164 In a recent analysis of 82 ALK-positive lung cancer patients, ALK tyrosine kinase inhibitor (crizotinib) therapy was associated with improved survival compared with that of crizotinib-naive controls. 166 Survival among ALK-positive patients who were given crizotinib in the second-line or third-line setting was significantly better than those patients given any second-line therapy (2-year survival, 55 vs 12%). However, unlike EGFR mutation, ALK rearrangement was not a favorable prognostic factor.…”
Section: Eml4-alk Rearrangement: Driver Mutation Of Lung Cancermentioning
confidence: 93%
“…However, unlike EGFR mutation, ALK rearrangement was not a favorable prognostic factor. 166 Dual-color-split-apart FISH is the recommended method for the EML4-ALK test. A positive test result in 415% of 50 analyzed tumor cells is the cutoff point recommended by the College of American Pathologist and the Association of Molecular Pathology.…”
Section: Eml4-alk Rearrangement: Driver Mutation Of Lung Cancermentioning
confidence: 99%
“…Over the past decade, research has demonstrated that the clinical benefit from targeted therapies is dependent upon our knowledge of the presence of specific genetic aberrations within the tumor (1)(2)(3)(4)(5)(6)(7)(8)(9). To maximize therapy efficacy, treatment must be tailored to the genetic milieu of a specific tumor, to deliver what is referred to as 'precision medicine'.…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the last 30 years, medical treatment for advanced SCLC has mainly remained unchanged, consisting of a platinum-based chemotherapy regimen with optional radiation therapy depending on tumor stage. 2 Although targeted therapeutic options have been established for pulmonary adenocarcinomas, including EGFR (epidermal growth factor receptor) and ALK (anaplastic lymphoma kinase) inhibitors, 1,3,4 and recently also for squamous cell carcinomas, 5,6 small-cell carcinomas still lack therapeutically exploitable genetic alterations. So far no single molecularly targeted drug has yet shown any significant clinical activity in SCLC.…”
mentioning
confidence: 99%